ChemInform Abstract: Directed Functionalization of 1, 2‐Dihydropyridines: Stereoselective Synthesis of 2, 6‐Disubstituted Piperidines. Issue 47 (6th November 2014) - Pelletier, Guillaume; Constantineau‐Forget, Lea; Charette, Andre B.
Abstract A rapid and stereoselective synthetic method for the generation of 2, 6‐cis‐disubstituted piperidines is reported.